Consensus Recommendations of the Multiple Sclerosis Study Group and the Portuguese Neuroradiological Society for the Use of Magnetic Resonance Imaging in Multiple Sclerosis in Clinical Practice: Part 2. - Pereira, Daniela Jardim (2020)
Introduction: Magnetic resonance imaging is recognized as the most important diagnostic test in the diagnosis of multiple sclerosis, differential diagnosis and evaluation of progression/therapeutic response. However, to make optimal use of magnetic resonance imaging in multiple sclerosis, the use of a standard, reproducible and comparable imaging protocol is of uttermost importance. In this context, the Portuguese Society of Neuroradiology and the Group of Studies of Multiple Sclerosis, after a joint discussion, appointed a committee of experts to create recommendations adapted to the national reality on the use of magnetic resonance imaging in multiple sclerosis. This document represents the second part of the first Portuguese consensus recommendations on the use of magnetic resonance imaging in multiple sclerosis in clinical practice.Material and Methods: The Portuguese Society of Neuroradiology and the Group of Studies of Multiple Sclerosis, after discussing the topic in national meetings and after a working group meeting held in Figueira da Foz, May 2017, appointed a committee of experts that have developed several standard protocols on the use of magnetic resonance imaging on multiple sclerosis by consensus. The document obtained was based on the best scientific evidence and expert opinion. Portuguese multiple sclerosis consultants and departments of neuroradiology scrutinized and reviewed the consensus paper; comments and suggestions were considered. Standardized strategies of magnetic resonance imaging referral in clinical practice for diagnosis and follow-up of multiple sclerosis were published in the first part of this paper.Results: We provide magnetic resonance imaging acquisition protocols regarding multiple sclerosis diagnostic and monitoring and the information to be included in the report for application across Portuguese healthcare institutions.Conclusion: We hope that these first Portuguese magnetic resonance imaging guidelines will contribute to optimize multiple sclerosis management and improve patient care in Portugal.